The assessment of changes in cognitive functioning in the elderly: age- and education-specific reliable change indices for the SIDAM - Stein, Janine; Weyerer, Siegfried (Dementia and geriatric cognitive disorders, 2012)
Background/Aims: The diagnostic criteria for dementia include reliable evidence of cognitive deterioration over time measured by cognitive tests. The Structured Interview for the Diagnosis of Dementia of the Alzheimer Type, Multi-infarct Dementia and Dementia of other Etiology according to DSM-III-R, DSM-IV and ICD-10 (SIDAM) is a neuropsychological instrument to determine cognitive status in patients with mild cognitive impairment (MCI) and dementia. Normative data for changes in cognitive functioning that normally occur in cognitively healthy individuals are required to interpret changes in SIDAM test scores. Methods: A sample of 1,090 cognitively healthy individuals participating in the German Study on Ageing, Cognition and Dementia in Primary Care Patients (AgeCoDe) aged 75 years and older was assessed four times at 1.5-year intervals over a period of 4.5 years using the SIDAM. Age- and education-specific reliable change indices (RCIs) accounting for probable measurement error and practice effects were computed for a 90% confidence interval. Results: Across different age and education subgroups, changes from at least 3-5 points indicated significant (i.e. reliable) changes in SIDAM test scores at the 90% confidence level. Conclusion: This study offers age- and education-specific normative data for the SIDAM based upon established RCI methods. The RCI scores provided in this study may help clinicians and researchers to interpret cognitive changes in SIDAM test scores and may contribute to the early detection and diagnosis of MCI and dementia in the elderly.